Shaping dental contract reform: a clinical and cost-effective analysis of incentive-driven commissioning for improved oral health in primary dental care. Issue 9 (8th September 2016) - Hulme, C; Robinson, P G; Saloniki, E C; Vinall-Collier, K; Baxter, P D; Douglas, G; Gibson, B; Godson, J H; Meads, D; Pavitt, S H
Abstract : Objective: To evaluate the clinical and cost-effectiveness of a new blended dental contract incentivising improved oral health compared with a traditional dental contract based on units of dental activity (UDAs). Design: Non-randomised controlled study. Setting: Six UK primary care dental practices, three working under a new blended dental contract; three matched practices under a traditional contract. Participants: 550 new adult patients. Interventions: A new blended/incentive-driven primary care dentistry contract and service delivery model versus the traditional contract based on UDAs. Main outcome measures: Primary outcome was as follows: percentage of sites with gingival bleeding on probing. Secondary outcomes were as follows: extracted and filled teeth (%), caries (International Caries Detection and Assessment System (ICDAS)), oral health-related quality of life (Oral Health Impact Profile-14 (OHIP-14)). Incremental cost-effective ratios used OHIP-14 and quality adjusted life years (QALYs) derived from the EQ-5D-3L. Results: At 24 months, 291/550 (53%) patients returned for final assessment; those lost to follow-up attended 6.46 appointments on average (SD 4.80). The primary outcome favoured patients in the blended contract group. Extractions and fillings were more frequent in this group. Blended contracts were financially attractive for the dental provider but carried a higher cost for the service commissioner. Differences in generic health-related quality of life were negligible. Positive changes over time in oral health-related quality of life in both groups were statistically significant. Conclusions: This is the first UK study to assess the clinical and cost-effectiveness of a blended contract in primary care dentistry. Although the primary outcome favoured the blended contract, the results are limited because 47% patients did not attend at 24 months. This is consistent with 39% of adults not being regular attenders and 27% only visiting their dentist when they have a problem. Promotion of appropriate attendance, especially among those with high need, necessitates being factored into recruitment strategies of future studies.